(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
In this study, the species composition, distribution dynamics and population structure of butterflies belonging to the family Nymphalidae (Lepidoptera) were investigated across different natural landscapes. The research was carried out in forest, steppe and mountain landscapes of the Samarkand, Jizzakh and Tashkent regions. According to the results, a total of 46 species were recorded, 18 species in Samarkand, 27 species in Jizzakh and 31 species in the Tashkent region. The highest species diversity was observed in foothill and forest-steppe biotopes. The ecological conditions of the landscapes, climatic factors and plant cover had a direct influence on the number and seasonal fluctuations of Nymphalidae populations.